2011
DOI: 10.1016/j.cmet.2011.05.008
|View full text |Cite
|
Sign up to set email alerts
|

Innervation Patterns of Autonomic Axons in the Human Endocrine Pancreas

Abstract: SUMMARY The autonomic nervous system regulates hormone secretion from the endocrine pancreas, the islets of Langerhans, and thus impacts glucose metabolism. The parasympathetic and sympathetic nerves innervate the pancreatic islet, but the precise innervation patterns are not known, particularly in human islets. Here we demonstrate that the innervation of human islets is different from that of mouse islets and that it does not conform to existing models of autonomic control of islet function. By visualizing ax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
292
4
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 297 publications
(326 citation statements)
references
References 41 publications
17
292
4
12
Order By: Relevance
“…Our results differ from previous observations made by Rodriguez-Diaz et al of the mouse islet sympathetic innervation: we reveal intra-islet TH + axons and varicosities and their connection/ elongation in space and contacts with capillaries, which are absent in the mouse islet images presented previously [23]. Because Rodriguez-Diaz et al found sympathetic neurovascular contacts in human islets, they proceeded to emphasise species differences in innervation patterns.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Our results differ from previous observations made by Rodriguez-Diaz et al of the mouse islet sympathetic innervation: we reveal intra-islet TH + axons and varicosities and their connection/ elongation in space and contacts with capillaries, which are absent in the mouse islet images presented previously [23]. Because Rodriguez-Diaz et al found sympathetic neurovascular contacts in human islets, they proceeded to emphasise species differences in innervation patterns.…”
Section: Discussioncontrasting
confidence: 57%
“…The potential reason for the discrepancy between the intra-islet TH + sympathetic innervation reported in this study and the lack of TH + signals inside mouse islets in the observations from Rodriguez-Diaz et al [23] might be due to the different optical properties of the islets used in the two studies. The transparent mouse islets that we prepared by optical clearing account for the detection of the TH + neurovascular complex in the islet core, whereas the untreated islets used in the study of Rodriguez-Diaz et al study are prone to losing fluorescent signals because of scattering in the tissue.…”
Section: Discussioncontrasting
confidence: 53%
See 2 more Smart Citations
“…In this issue of Diabetologia, Carol Yang, Quin Wills and Jim Johnson systematically evaluate the beta cell-protective properties of an extensive panel of over 200 factors on primary mouse beta cells [4]. These factors were selected on the basis of the expression of their cognate receptors in mouse or human islets, derived from prior work by the authors [5] among many others [6][7][8][9][10]. Recognising that beta cell stress in diabetes can occur in many different shapes and forms [3], each factor was systematically evaluated in five distinct islet cell culture conditions, reflective of different type 1 or type 2 diabetes-associated stresses.…”
Section: Gfpmentioning
confidence: 99%